2022
DOI: 10.1001/jamaoncol.2022.2421
|View full text |Cite
|
Sign up to set email alerts
|

Novel Quadruplets and the Age of Immunotherapies in the Treatment of Newly Diagnosed Multiple Myeloma

Abstract: Multiple myeloma (MM) is the second most common hematologic cancer, with an estimated worldwide incidence of over 175 000 newly diagnosed patients annually and over 130 000 patients living with the disease in the US. 1 Although there is not yet an established curative therapy, the past couple of decades have been heralded by the development of novel therapeutics translating into patients with myeloma living longer. This is especially highlighted by the US Food and Drug Administration (FDA) approvals of the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…30 As we and others have shown that high rates of MRD negativity and sustained MRD negativity are achieved with extensive quadruplet treatment approaches, it is time to re-evaluate the role of high-dose melphalan, especially considering recent findings of significantly increased mutational burden and detrimental long-term effects of genomic damage. [32][33][34][35] In the near future, consequent implementation of T-cell engaging strategies in frontline treatment with CAR-T cell application replacing high-dose melphalan or use of bispecific antibodies in maintenance strategies will allow further treatment optimization and are expected to achieve unprecedented high MRD negativity and sustained MRD negativity rates. standard-of-care arm was ethically not justifiable.…”
Section: Discussionmentioning
confidence: 99%
“…30 As we and others have shown that high rates of MRD negativity and sustained MRD negativity are achieved with extensive quadruplet treatment approaches, it is time to re-evaluate the role of high-dose melphalan, especially considering recent findings of significantly increased mutational burden and detrimental long-term effects of genomic damage. [32][33][34][35] In the near future, consequent implementation of T-cell engaging strategies in frontline treatment with CAR-T cell application replacing high-dose melphalan or use of bispecific antibodies in maintenance strategies will allow further treatment optimization and are expected to achieve unprecedented high MRD negativity and sustained MRD negativity rates. standard-of-care arm was ethically not justifiable.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] However, there are efforts underway to reduce toxicity by tailoring or tapering treatment in patients who have little or no detectable measurable residual disease (MRD). [ 10 ] As a result, accurate detection of small amounts of disease will become increasingly important for this growing patient population. Also, efforts are underway to increase CD38 expression on MM cells by treatment with agents such as all‐trans retinoic acid (ATRA) to take advantage of the excellent anti‐CD38 therapeutic options available.…”
Section: Introductionmentioning
confidence: 99%